Theatre Marketing – Analysis of Customers’ Satisfaction - Šimić, Mirna Leko; Pap, Ana (Marketing & Menedzsment, 2020)
THE AIMS OF PAPER The aim of this paper was to identify key elements that create satisfaction of classic theatre audiences with respect to age (young (<35) vs. senior (35+) and theatre visiting frequency. It was measured as discrepancies between the level of theatre attendants’ expectations from certain dimensions of theatre service and their experience evaluation with the same. METHODOLOGY The research was conducted on a convenient sample using an in-person method in two different intervals: in the first interval research was conducted on young respondents (18-34) and in second interval research was conducted on senior respondents (age 35+). MOST IMPORTANT RESULTS The study has identified that the general major source of dissatisfaction with Croatian National Theatre in Osijek (HNK Osijek) are repertoire and the different experience offered. These are the dimensions HNK Osijek should focus its efforts on. Also, this study confirms that HNK Osijek customers' perception of importance of different elements that create its marketing profile and their satisfaction with those differ with respect to age and theatre attendance frequency. The most critical segment in terms of satisfaction are the senior occasional visitors, where the discrepancies between the expectations and experiences are highest in general.